Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/1759-7714.13566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genetic variation in Notch regulator DTX1 on SCLC prognosis compared with the effect on NSCLC prongosis

Abstract: Deltex‐1 (DTX1) is a negative regulator of the Notch signaling pathway. Here, we investigated the clinical effect of DTX1 rs1732786A > G, which is associated with better prognosis in patients with early‐stage non‐small cell lung cancer (NSCLC), in 261 patients with small cell lung cancer (SCLC). DTX1 rs1732786A > G was associated with a significantly worse chemotherapy response and lower overall survival in the codominant model (odds ratio = 0.42, 95% confidence interval [CI]: 0.26–0.66, P = 2 × 10−4; hazard r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In contrast, patients with small cell lung cancer (SCLC) carrying DTX1 mutations showed a worse response to chemotherapy and a lower OS rate, suggesting that mutations in the same gene may play opposite roles in different subtypes of malignant tumors in the same organ. The specific mechanisms underlying these mutations remain to be determined ( Yoo et al, 2020 ).…”
Section: Functions and Associated Molecular Mechanisms Of The Dtx Familymentioning
confidence: 99%
“…In contrast, patients with small cell lung cancer (SCLC) carrying DTX1 mutations showed a worse response to chemotherapy and a lower OS rate, suggesting that mutations in the same gene may play opposite roles in different subtypes of malignant tumors in the same organ. The specific mechanisms underlying these mutations remain to be determined ( Yoo et al, 2020 ).…”
Section: Functions and Associated Molecular Mechanisms Of The Dtx Familymentioning
confidence: 99%
“…It has been reported that DTX1 is a potential biomarker for GBM diagnosis (8). Mutations of DTX1 are associated with poor prognosis in patients with small cell (11). In the present study, we explored the associations between DTX1 and BC, and found lower DTX1 could promote BC cell proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 77%